Agro-Tourism Development Strategy in Desa Wisata Kaligono (Dewi Kano) of Kaligesing District of Purworejo Regency - Siwi Harning Pambudi; Sunarto Sunarto; Prabang Setyono (Agriekonomika, 2018)
This research aims were: to gain information about villagers’ perception concerning to the plan of building an agro-tourism area in Dewi Kano, to find out the side effect of agro-tourism, to formulate the strategy in developing the agro-tourism. Researcher used observation, interview, questionnaire, and SWOT analysis (in formulating the agro-tourism development strategy) as methods. The results of the research show that the villagers of Dewi Kano are supporting the plan of developing their area as an agro-tourism; this is seen from their perceptions which tend to agree, because they understand that agro-tourism development can give benefits in ecology, economy, social, and management. The strategy which can be applied in developing agro-tourism of Dewi Kano is a progressive strategy; it means, the research location is in a great condition, so it will be well-developed by maximizing the opportunities.